Dampak Pemekaran Nagari Dalam Meningkatkan Pelayanan Publik Kepada Masyarakat - Beni Mulia; Syafruddin Ritonga; Irwan Nasution (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2021)
The total population of 47,642 people is not effective if only one Nagari/Village is served, so expansion is believed to be one solution that can handle the problem of suboptimal services. In addition to expansion, excellent service must also be implemented, excellent service can be assessed from the following indicators: simplicity, clarity and certainty, security, openness, efficiency, economy, equitable justice, punctuality. From the description above, the author conducted research on the impact of the expansion of Nagari in improving public services to the people of Nagari Ujung Gading, Lembah Melintang District, West Pasaman Regency. The formulation of the research problem that became the author's reference is How the Impact of the Expansion of Nagari in Improving Public Services to the People of Nagari Ujung Gading, Lembah Melintang District, West Pasaman Regency. This research is a qualitative research with data collection techniques using literature and field research such as interviews, observations, documentation. Data analysis using the cycle method from Miles and Hubermann, namely data reduction, data presentation, and conclusion drawing. Research informants are Wali Nagari Ujung Gading, Head of Government of Nagari Ujung Gading, Nagari Ujung Gading Community. The result of the research is that the expansion has no impact on the service, because the service is in accordance with the indicators of excellent service.